The role of the cartilaginous to osseous acetabular angle ratio in children with developmental dysplasia of the hip - Wang, Jiaqi; Li, Tianyou; Yao, Yangyang; Lu, Chaoqun; Wang, Yanzhou (Frontiers in Pediatrics, 2024)
This study aims to demonstrate the use of the cartilaginous to osseous acetabular angl e ratio in surgical decision making for hip dysplasia.Data was collected from patients who underwent MRI scanning of the hip after conse rvative treatment for DDH between August 2019-2022.The data included demographic information as well as anteroposterior pelvic radiograph. OAI (osseous acetabular inde x) was measured using X-ray, while CAI (cartilaginous acetabular index) and CAHI (c artilaginous acetabulum head index) were measured using MRI. The square of CAI to OAI, AAR (acetabular angle ratio) was calculated. The RHD (residual hip dysplasia) group was categorized as OAI above 20°. During the postoperative follow-up, we eval uated the patients who underwent Bernese triple pelvic osteotomy in RHD group. The surgical patients with observation period exceeded 1 year were collected and analyzed. The distribution of AAR among the different groups was analyzed. A ROC predictive model was constructed using the AAR of the patients in the normal and surgical grou p to evaluate the need of surgery.There was a significant difference in OAI, CAI, CAHI, AAR between the RHD group (OAI 26.15±3.90°, CAI 11.71±4.70°, CAHI 79.75±6.27％ and AAR 5.88±4.24) and t he control group (OAI 16.77±5.39°, CAI 6.16±3.13°, CAHI 85.05±4.91％ and AAR 2. 71±2.08) (p<0.001). 93.5% of control group had an AAR ≤5, while only 6.5% had an AAR >5. Postoperative imaging follow-up was excellent in 52 and good in 3 cases, while functional follow-up was excellent in 53 and good in 2 cases. In 15 patients, th e observation period exceeded 1 year. The mean observation period was 633.1±259.6 days. And the preoperative CAHI was 71.7±4.8%. Of the patients with AAR ＞ 5, a s ubstantial 94.8% (55/58) had undergone surgery, while all patients with AAR less than or equal to 5 had not undergone surgery (91/91). Based on the ROC, a cut-off value of 5.09 was identified for need of surgery in children with RHD.Surgical decision for residual hip dysplasia can be referred to the AAR. AAR ＞ 5 m ay be a potential indicator for surgical intervention in cases of RHD.